PERAN GURU SEBAGAI ROLE MODEL MENURUT KONSEP ALBERT BANDURA DALAM MENERAPKAN KURIKULUM 2013 - SITI HAWA (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2020)
This research is entitled "the role of the teacher as a role model according to the Albert Bandura concept in implementing the 2013 curriculum" while the problem in this study is how the role of the teacher as a role model according to the Albert Bandura concept in implementing the 2013 curriculum and the Albert Bandura concept of the teacher as a role model in implementing curriculum 2013. in this study the author uses the method of Library Research and Fild research and in accordance with the topic of this discussion, the Al-Quran and a number of books related to the role of teachers as role models according to Albert Bandura in implementing The 2013 curriculum, scientific writings and other literature related to the role of teachers as role models according to Albert Bandura in implementing the 2013 curriculum. The importance of the role of teachers as role models for students is related to character personalities to help build the character of students. Character education can be implemented through existing programs in schools, such as integrating character education in learning and implementing character education through extracurricular activities. In this case, the role of the teacher is not only to educate students according to the demands of the curriculum, but also to personally provide an example to students by becoming a role model of individual characters. Teachers who become role models will be able to show attitudes and behaviors that are in accordance with the values ​​and norms in everyday life so that students can see and imitate them. The role of teachers as individual character role models will support character education programs and help students to have good character personalities.